MULTILATERAL COOPERATION IN THE BLACK SEA REGION IN THE ENERGY FIELD - Andrey Vyacheslavovich Ishin (Проблемы постсоветского пространства)
In the article the state of international cooperation is analysed in the field of energy in Black Sea besseyne. Problems and prospects of development of power communications, their influence, are examined on the level of international stability.